The Political Economic Climate of Advancement In India Since Freedom! : a Case Study of Smt. Indira Gandhi: The Influence of Indira Gandhi on India's Political Economy (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Popularly known as the Iron Lady of India, Indira Gandhiearned a formidable reputation across the globe as a 'statesman'. Her sheersense of politics and exceptional skills catapulted her position in the Indianpolitics, so much so that she went on to become the first woman elected to heada democratic country. Till date, she is the only woman to hold the office. Bornin a politically influential dynasty and growing in an intense politicalatmosphere, Indira Gandhi had learned the trick of the trade quite early inlife. She possessed an authoritarian streak and became the central figure ofthe Indian National Congress party, post her father's death. She was known forher political ruthlessness and extraordinary centralization of power. It wasduring her premiership that India became the regional power in South Asia withconsiderable political, economic, and military clout. She also presided over astate of emergency and made considerable changes to the Indian Constitution.She used the army to resolve numerous internal disputes and encouraged aculture of sycophancy and nepotism, due to which she rubbed many Indians on thewrong side. Gandhi initialized the Operation Blue Star, which gave her acritical reputation and eventually scripted her assassination.